Place, exclusion, and mortgage markets - Aalbers, Manuel (Malden : Wiley-Blackwell, 2011)
"Just as in society, the mortgage market may exclude people on the basis of place, as well as race. Place-based exclusion in the mortgage market often takes the form of "redlining," a tacit agreement among lending institutions to delineate sections of cities into areas where no home mortgages are to be issued. Place, Exclusion and Mortgage Markets presents an in depth examination of the practice of redlining and the broader implications of contemporary urban exclusion processes. Through a careful balance of comparative research and literature reviews, author Manuel B. Aalbers reveals how redlining, which is most visible at the urban level, is also constituted at the interaction of several spatial scales: neighborhood, urban, regional, national, and global. By utilizing several research strategies and presenting documented evidence from various urban sectors in the United States, Italy, and the Netherlands, this book offers fresh insights and much needed analytical clarity to shape our understanding of redlining and other urban exclusion processes"--
Machine generated contents note: Preface. -- Introduction. -- Part I The Exclusion, Urban and Market Lenses. -- 1 Social and Financial Exclusion. -- 1.1 Social Exclusion. -- 1.2 Financial Exclusion. -- 1.3 How Space and Housing enter the Idea of Exclusion. -- 2 A Socio-Spatial Approach. -- 2.1 David Harvey, Capital Switching and Urban Development. -- 2.2 A Socio-Spatial Approach to Urban Development. -- 2.3 Exploratory Comparative Research with Contrasting Cases. -- 3 Markets, Institutions, Risk, Credit Scoring. -- 3.1 The Market as an Institution. -- 3.2 Homeownership in the Risk Society. -- 3.3 Risk Selection and Credit Scoring. -- 3.4 Difficulties and Risk. -- Part II Redlining Research in the US, Italy and the Netherlands. -- 4 The US: One Century of Redlining. -- 4.1 On the Origins of Mortgage Markets and Redlining. -- 4.2 Redlining Research Since the 1970s. -- 4.3 Redlining Readdressed. -- 4.4 The Rise of Securitization and Subprime Lending. -- 5 Italy: Capital Switching in Milan. -- 5.1 Housing in Italy. -- 5.2 The Italian Mortgage Market. -- 5.3 Economy, Migrants and Housing in Milan. -- 5.4 The Milanese Geography of Access to Mortgage Loans. -- 5.5 Capital Switching in Milan. -- 6 The Netherlands: Colored Maps. -- 6.1 Housing in the Netherlands. -- 6.2 The Dutch Mortgage Market. -- 6.3 Ethnic Minorities and Discrimination. -- 6.4 The Socio-Spatial Structure of Rotterdam. -- 6.5 The Colored Map of Rotterdam (1980-1999). -- 6.6 Rotterdam versus Amsterdam (1999-2001). -- 6.7 Rotterdam, The Hague and Arnhem (2005-2006). -- 6.8 Redlining Redux: Rotterdam and The Hague in the Financial Crisis (2008-2010). -- Photo Essay The Tarwewijk, Rotterdam. -- Part III Conclusions. -- 7 The Globalization of Redlining? -- 7.1 Redlining in the US. -- 7.2 Credit Scoring: The Silent Globalization of the Mortgage Market. -- 7.3 City Forces. -- 7.4 Neighborhood Forces. -- 7.5 National Forces. -- 7.6 Markets and Institutions Preventing Redlining. -- 7.7 The Endemic Nature of Redlining. -- References. -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Discrimination in mortgage loans -- Case studies; Mortgages -- Case studies; Marginality, Social -- Case studies; Business; BUSINESS & ECONOMICS -- Real Estate -- Mortgages; Discrimination in mortgage loans; Marginality, Social; Mortgages; Electronic books; Case studies